Facile Oxidative Desulfurisation of Benzothiophene Using Polyoxometalate H4[α-SiW12O40]/Zr Catalyst - Aldes Lesbani Aldes Lesbani; Agnes Agnes; Randi O. Saragih; Marieska Verawaty; Risfidian Mohadi; Hilda Zulkifli (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
A highly active catalyst H4[α-SiW12O40]/Zr based polyoxometalete Keggin type was prepared by wet impregnation method and was characterized by FTIR spectroscopy, X-ray diffractometer, surface textural property by SEM, and analysis of porosity by BET method. H4[α-SiW12O40]/Zr was successfully synthesized and showed uniform properties with block solid structure which was applied as heterogeneous stable catalyst for oxidative desulfurization of benzothiophene under simple and mild condition using H2O2 as oxidant. Facile conversion of benzothiophene to sulfone by using heterogeneus H4[α-SiW12O40]/Zr catalyst up to 99% was observed to show the active catalytically. Keggin H4[α-SiW12O40]/Zr cage structure after reaction was different from fresh catalyst which was indicated by the instability of H4[α-SiW12O40]/Zr under reaction condition. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)